Pilot Study on the Use of a Laser-Structured Double Diamond Electrode (DDE) for Biofilm Removal from Dental Implant Surfaces - Koch, Maximilian; Burkovski, Andreas; Zulla, Manuel; Rosiwal, Stefan; Geissdorfer, Walter; Dittmar, Roman; Grobecker-Karl, Tanja (Journal of Clinical Medicine, 2020)
No proper treatment option for peri-implantitis exists yet. Based on previous studies showing the in vitro effectiveness of electrochemical disinfection using boron-doped diamond electrodes, novel double diamond electrodes (DDE) were tested here. Using a ceramic carrier and a laser structuring process, a clinically applicable electrode array was manufactured. Roughened metal discs (n = 24) made from Ti-Zr alloy were exposed to the oral cavities of six volunteers for 24 h in order to generate biofilm. Then, biofilm removal was carried out either using plastic curettes and chlorhexidine digluconate or electrochemical disinfection. In addition, dental implants were contaminated with ex vivo multispecies biofilm and disinfected using DDE treatment. Bacterial growth and the formation of biofilm polymer were determined as outcome measures. Chemo-mechanical treatment could not eliminate bacteria from roughened surfaces, while in most cases, a massive reduction of bacteria and biofilm polymer was observed following DDE treatment. Electrochemical disinfection was charge- and time-dependent and could also not reach complete disinfection in all instances. Implant threads had no negative effect on DDE treatment. Bacteria exhibit varying resistance to electrochemical disinfection with Bacillus subtilis, Neisseria sp., Rothia mucilaginosa, Staphylococcus haemolyticus, and Streptococcus mitis surviving 5 min of DDE application at 6 V. Electrochemical disinfection is promising but requires further optimization with respect to charge quantity and application time in order to achieve disinfection without harming host tissue.
CRIS-Team WoS Importer:2020-11-06